Effectiveness of preoperative autologous blood donation for protection against allogeneic blood exposure in adult spinal deformity surgeries: a propensity-matched cohort analysis - Kelly, Michael P. (J Neurosurg Spine, 2015)
OBJECT: The goal of this study was to examine the effectiveness of preoperative autologous blood donation (PABD) in adult spinal deformity (ASD) surgery. METHODS: Patients undergoing single-stay ASD reconstructions were identified in a multicenter database. Patients were divided into groups according to PABD (either PABD or NoPABD). Propensity weighting was used to create matched cohorts of PABD and NoPABD patients. Allogeneic (ALLO) exposure, autologous (AUTO) wastage (unused AUTO), and complication rates were compared between groups. RESULTS: Four hundred twenty-eight patients were identified as meeting eligibility criteria. Sixty patients were treated with PABD, of whom 50 were matched to 50 patients who were not treated with PABD (NoPABD). Nearly one-third of patients in the PABD group (18/60, 30%) did not receive any autologous transfusion and donated blood was wasted. In 6 of these cases (6/60, 10%), patients received ALLO blood transfusions without AUTO. In 9 cases (9/60, 15%), patients received ALLO and AUTO blood transfusions. Overall rates of transfusion of any type were similar between groups (PABD 70% [42/60], NoPABD 75% [275/368], p = 0.438). Major and minor in-hospital complications were similar between groups (Major PABD 10% [6/60], NoPABD 12% [43/368], p = 0.537; Minor PABD 30% [18/60], NoPABD 24% [87/368], p = 0.499). When controlling for potential confounders, PABD patients were more likely to receive some transfusion (OR 15.1, 95% CI 2.1–106.7). No relationship between PABD and ALLO blood exposure was observed, however, refuting the concept that PABD is protective against ALLO blood exposure. In the matched cohorts, PABD patients were more likely to sustain a major perioperative cardiac complication (PABD 8/50 [16%], NoPABD 1/50 [2%], p = 0.046). No differences in rates of infection or wound-healing complications were observed between cohorts. CONCLUSIONS: Preoperative autologous blood donation was associated with a higher probability of perioperative transfusions of any type in patients with ASD. No protective effect of PABD against ALLO blood exposure was observed, and no risk of perioperative infectious complications was observed in patients exposed to ALLO blood only. The benefit of PABD in patients with ASD remains undefined.